Welfare migration or migrant selection? Social insurance participation and rural migrants’ intentions to seek permanent urban settlement in China - Xie, Shenghua; Chen, Juan; Ritakallio, Veli-Matti; Leng, Xiangming (Urban studies (Edinburgh, Scotland), 2021)
The welfare system can be a crucial factor in the urban settlement of rural migrants, but its effects are difficult to determine because to do so one must distinguish the effect of welfare entitlement from the effect of ‘migrant selectivity bias’, which widely exists in cities in developing countries. Using survey data from 15 Chinese cities, this study examines the ways in which social insurance – the most critical social welfare package in China – affects rural migrants’ urban-settlement intentions. The results show that there is a ‘migrant selectivity bias’ in Chinese cities, that is, rural migrants who are better off socio-economically are more inclined to participate in social insurance and are more inclined to pursue permanent urban settlement. Meanwhile, social insurance participation is significantly and positively related to rural migrants’ urban-settlement intentions, and this positive relation remains even after we discount the effect of ‘migrant selectivity bias’ in the analysis. We argue that, for rural migrants in China, the effect of social insurance participation on urban settlement intentions closely resembles that experienced by those who move to migration-managed regimes. We conclude that the Chinese government should establish a more inclusive social welfare system to enable rural migrants to permanently settle in cities. 福利制度可能是农村移民在城市定居的一个关键因素，但其影响很难确定，因为要做到这一点，必须将福利待遇的影响与发展中国家城市普遍存在的“移民选择性偏见”的影响区分开来。利用来自中国15个城市的调查数据，本研究考察了社会保险（中国最重要的社会福利一揽子计划）如何影响农村移民的城市定居意向。结果表明，中国城市存在“移民选择性偏见”，即社会经济条件较好的农村移民更倾向于参加社会保险，更倾向于寻求永久性的城市定居。同时，参与社会保险与农民工的城市定居意愿显著正相关，即使我们在分析中忽略“移民选择性偏见”的影响，这种正相关仍然存在。我们认为，对于中国的农村移民来说，参加社会保险对城市定居意愿的影响非常类似于那些向移民管理体制迁移的人所经历的影响。我们的结论是，中国政府应该建立一个更具包容性的社会福利体系，让农村移民能够永久定居城市。